A new species of Tetragonopterus Cuvier, 1816 (Characiformes, Characidae, Tetragonopterinae) from the upper rio Araguaia Central Brazil - Silva, Gabriel S. C. [UNESP]; Benine, Ricardo C. [UNESP] (Magnolia Press, 2011)
A new characid, Tetragonopterus anostomus, is described from the upper rio Araguaia, Central Brazil. The new species is distinguished from its congeners (T. argenteus, T. carvalhoi, T. chalceus e T. rarus) by traits related to the position of the mouth, number of premaxillary teeth, number of predorsal scales, overall color pattern, and number of gill rakers. A brief discussion on its putative ecomorphological adaptations is provided. © 2011 Magnolia Press.
Keywords: Freshwater; Neotropical region; Taxonomy; Tetragonopterus chalceus